2015
DOI: 10.1111/petr.12544
|View full text |Cite
|
Sign up to set email alerts
|

Australian deceased donor kidney allocation protocols: Transplant waiting and graft quality for children and adolescents

Abstract: DD kidney allocation protocols may influence timing of transplantation and graft quality for pediatric recipients. This study aimed to evaluate the effects of these protocols, including pediatric priority, on waiting time on dialysis, transplant type, donor age, and HLA matching according to state of transplant in Australia. De-identified information on patients <15 yr of age who commenced RRT in NSW, Qld, and Victoria from 2002 to 2011 was retrieved from the ANZDATA. Transplant type, donor age, and HLA mismat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Likelihood and rate of transplantation varied significantly by region in the US 27,61,62 . Geographic variations in the incidence of transplant were similarly observed in Brazil, 56 as well as differences in donor characteristics and time to transplant across regions of Australia 63 . Few studies examined interactions between geographic regions and other SDoH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likelihood and rate of transplantation varied significantly by region in the US 27,61,62 . Geographic variations in the incidence of transplant were similarly observed in Brazil, 56 as well as differences in donor characteristics and time to transplant across regions of Australia 63 . Few studies examined interactions between geographic regions and other SDoH.…”
Section: Resultsmentioning
confidence: 99%
“…27,61,62 Geographic variations in the incidence of transplant were similarly observed in Brazil, 56 as well as differences in donor characteristics and time to transplant across regions of Australia. 63 Few studies examined interactions between geographic regions and other SDoH. One study found no differences in rates of transplant when comparing White children and those of other identified racial or ethnic identity in the Midwestern US, 64 while another found regions in the US with the longest wait times also had the highest percentage of Hispanic children.…”
Section: Listing Regionmentioning
confidence: 99%
“…A study conducted in Australia and New Zealand examining the influence of deceased donor kidney allocation protocols, also found shorter waiting times 18 . However, this reduction in time to transplant is variable among developing countries.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, other factors were found to impact time to transplant, such as age at kidney failure, since children reaching stage 5 CKD before the age of 12 waited significantly longer for transplantation. Similarly, Le Page et al 18 identified recipient age as an important factor influencing timing of renal transplantation, noting that renal transplantation in young infants is rarely viable. In a study by our group, higher age at time of registration of pediatric patients on the transplant list was detected as a factor associated with greater probability of access to deceased donor transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation